1995
DOI: 10.1006/dbio.1995.1264
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Independent, Meiotic Spindle-Dependent Metaphase-to-Interphase Transition in Phorbol Ester-Treated Mouse Eggs

Abstract: Mouse eggs, arrested at metaphase II of meiosis, form pronuclei as a result of fertilization or exposure to parthenogenetic agents, such as the phorbol ester phorbol myristate acetate (PMA). Exposure of eggs to the microtubule inhibitor colcemid caused the disappearance of the meiotic spindle and prevented the PMA-induced release from metaphase. However, colcemid- and PMA-treated eggs which lacked spindles formed nuclei when treated in addition with the protein synthesis inhibitor cycloheximide or the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
1
26
1
Order By: Relevance
“…This is so because it is well known that if arrested into a metaphase-like stage, fertilized eggs can continue to oscillate for nearly 20 h (Day et al 2000), whereas under natural conditions, the oscillations cease by the approximate time of PN formation (Jones et al 1995). Hence, to extend these findings, we performed that same experimental design but in the presence of 100 ng/ml colcemid, which is known to prevent MII exit (Jones et al 1995, Moses & Kline 1995, Gordo et al 2002. Under these conditions, oscillations in enucleated eggs persisted in excess of 8 h ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is so because it is well known that if arrested into a metaphase-like stage, fertilized eggs can continue to oscillate for nearly 20 h (Day et al 2000), whereas under natural conditions, the oscillations cease by the approximate time of PN formation (Jones et al 1995). Hence, to extend these findings, we performed that same experimental design but in the presence of 100 ng/ml colcemid, which is known to prevent MII exit (Jones et al 1995, Moses & Kline 1995, Gordo et al 2002. Under these conditions, oscillations in enucleated eggs persisted in excess of 8 h ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence also suggests that PKC is involved in regulating sperminduced calcium oscillations by exerting a negative f e e d b a c k e f f e c t o n c a l c i u m r e l e a s e [ 8 0 ] . Furthermore, PKC has been implicated in the resumption of meiosis [81], cortical granule exocytosis [82][83][84] and pronuclear formation [85,86] in artificially activated oocytes. However, other evidence suggests that a different calciumdependent pathway, involving calmodulin and CaMKII, is responsible for the resumption of meiosis at fertilization [87].…”
Section: The Role Of Calcium At Activationmentioning
confidence: 99%
“…Treatment of mouse eggs with thimerosal caused repetitive calcium transients and cortical granule exocytosis, but these eggs remained at metaphase because thimerosal also disrupts the spindle [31]. The importance of meiotic spindle assembly for the exit from metaphase induced by PKC activation has also been proposed [32]. Recently it was reported that colcemid-treated eggs that were fertilized or treated with A23187 remained arrested at metaphase, but when the above-treated eggs were further exposed to 6-DMAP, they entered interphase [25].…”
Section: The Relationship Among Protein Kinase Activity Spindle Morpmentioning
confidence: 99%